Significance of the electromyographic analysis of the upper limb muscles of cricket bowlers: Recommendations from studies of overhead-throwing athletes - Nizam Uddin, Ahamed (World Scientific Publishing Company., 2015)
Link to publisher's homepage at http://www.worldscientific.com/